Impact of social protection programs on adults diagnosed with Tuberculosis: systematic review - Francisca Bruna Arruda Aragão; Ricardo Alexandre Arcêncio; Miguel Fuentealba-Torres; Tânia Silva Gomes Carneiro; Ludmilla Leidianne Limíro Souza; Yan Mathias Alves; Regina Célia Fiorati (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the impact of social protection programs on adults diagnosed with Tuberculosis. Methods: systematic review conducted by PRISMA, with registration PROSPERO CRD42019130884. The studies were identified in the VHL, PubMed, Scielo, CINAHL and Scopus databases, using the descriptors "Social Protection" and "Tuberculosis", in combination with keywords combined with Boolean operators AND and OR. Observational and interventional studies published until October 23, 2019, in Portuguese, English and Spanish, were included. Results: social protection programs improve the treatment of tuberculosis, cure rates, adherence to treatment, the provision of services for the control of TB and reduce poverty. Conclusions: social protection programs have a positive impact on the treatment and control of people diagnosed with Tuberculosis.